2021
DOI: 10.1177/23477989211017567
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media in Teaching High School Students: A Case of United Arab Emirates

Abstract: The use of social media platforms by the education sector has grown significantly in the past decade. The advancement in information and technology has prompted the integration of social media use in education. Social media use has revolutionized the learning processes from what was traditionally teacher-centered to the current student-centered approach. People between 16 and 24 years of age are considered among the active users of social media; hence, by incorporating an important part of their lives in schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Yunus et al, (2019) also reported that the advantage of social media helps develop students' writing ability. Jenaibi and Mansoori (2022) contended that social media context allows learners to manage and maintain a learning space that facilitates their learning activities and connections to peers and social networks across time and place. To achieve this aim, the present work specifically seeks to investigate the following research objectives.…”
Section: Social Media and Learning Foreign Languagesmentioning
confidence: 99%
“…Yunus et al, (2019) also reported that the advantage of social media helps develop students' writing ability. Jenaibi and Mansoori (2022) contended that social media context allows learners to manage and maintain a learning space that facilitates their learning activities and connections to peers and social networks across time and place. To achieve this aim, the present work specifically seeks to investigate the following research objectives.…”
Section: Social Media and Learning Foreign Languagesmentioning
confidence: 99%
“…As Information and Communication Technologies (ICTs) like social media get used more in classrooms, teachers need to understand the platforms to support teaching (Jenaibi and Mansoori, 2021). For example, secondary school teachers in Nigeria have used Facebook, WhatsApp, Twitter, and YouTube as interactive teaching and learning channels for communication and to share information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides being competent in their subject's content, teachers need to be comfortable executing pedagogical methods that are relevant in the 21st century (Moodley, 2019). Teachers from disadvantaged schools with limited ICT resources tend to not have the expertise or skills needed to effectively use ICT for teaching (Jenaibi and Mansoori, 2021). These teachers tend to resist using ICT (Jenaibi and Mansoori, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no studies have been undertaken from an information behaviour perspective; and whilst insights can be drawn from other disciplines (e.g. Media and Middle Eastern studies), some studies involving both male and female participants provide no breakdowns by gender [6][7][8].…”
Section: Previous Studiesmentioning
confidence: 99%